2014
DOI: 10.4314/ahs.v13i4.44
|View full text |Cite
|
Sign up to set email alerts
|

Stray dog trade fuelled by dog meat consumption as a risk factor for rabies infection in Calabar, southern Nigeria

Abstract: Background: Rabies is a preventable zoonosis with the highest case fatality of any disease in the world. In the developing world, it is transmitted mainly by dog bites. In parts of southern Nigeria, dog meat is a delicacy. Objective: To highlight trade in stray dogs as a major risk factor for rabies in animals and humans in south-south Nigeria. Method: Patients admitted into the University of Calabar Teaching Hospital (UCTH) with a diagnosis of rabies between July and October 2012 were analysed for risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…However, in the case of Makurdi, due to the high dog population and the poor acceptability of dog as meat for human consumption by indigenous tribes (Akombo, 2009), some southern states like Cross River (Ekanem et al, 2013), Enugu and Akwa Ibom states, source for dogs for human consumption from Makurdi and its environs. Therefore, the presence of the rabies antigen in the brain tissue of these dogs poses a risk of possible spread of the disease to other states since the dog trade and movement is not regulated by government.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of Makurdi, due to the high dog population and the poor acceptability of dog as meat for human consumption by indigenous tribes (Akombo, 2009), some southern states like Cross River (Ekanem et al, 2013), Enugu and Akwa Ibom states, source for dogs for human consumption from Makurdi and its environs. Therefore, the presence of the rabies antigen in the brain tissue of these dogs poses a risk of possible spread of the disease to other states since the dog trade and movement is not regulated by government.…”
Section: Discussionmentioning
confidence: 99%
“…On prevalence across the country, lower prevalence was commonly reported in the North [23][24][25] than in the South (Table 1) such that in a study, 85% prevalence was found in a community in Niger Delta [9]. In this region, dogs are slaughtered for food [33,40,76]; therefore, there is high demand for dog meat and consequently increase in dog rearing activities constituting a risk to an increase in disease prevalence and distribution. Also, disparity in dog density between the North and South could provide a possible explanation to the differences in prevalence between both regions [40,56,76].…”
Section: Prevalence In Animalsmentioning
confidence: 99%
“…Dogs sold for slaughter are usually not fed, this can enhance meat quality in terms of longer shelf life due to absence of gut content contamination of carcass during evisceration, consistent with the report of Sofos et al (1999). Changing such belief among butchers may pose a challenge, as slaughter points for dogs are usually located in hidden areas, consistent with the findings of Ekanem et al (2013) and the fact that dog meat consumption is regarded by many people as unethical and taboo on several grounds (Garba et al, 2013). However, only a small number 1.7% of butchers agree to the use of the suffocation method.…”
Section: Resultsmentioning
confidence: 63%